2009
DOI: 10.1523/jneurosci.0870-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reggies/Flotillins Regulate Retinal Axon Regeneration in the Zebrafish Optic Nerve and Differentiation of Hippocampal and N2a Neurons

Abstract: The reggies/flotillins-proteins upregulated during axon regeneration in retinal ganglion cells (RGCs)-are scaffolding proteins of microdomains and involved in neuronal differentiation. Here, we show that reggies regulate axon regeneration in zebrafish (ZF) after optic nerve section (ONS) in vivo as well as axon/neurite extension in hippocampal and N2a neurons in vitro through signal transduction molecules modulating actin dynamics. ZF reggie-1a, -2a, and -2b downregulation by reggie-specific morpholino (Mo) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 47 publications
(60 reference statements)
7
116
0
Order By: Relevance
“…Recent studies have confirmed the relevance of flotillins for axon regeneration in zebrafish as well as in mammalian cell cultures. Apparently, downregulation of flotillins by flotillin specific morpholinos in the zebrafish resulted in a massive reduction in the number of regenerating axons (60). Since the role of flotillins in neuronal regeneration has recently been directly reviewed, we here omit a long discussion of the topic.…”
Section: In Search Of the Molecular Function Of Flotillinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed the relevance of flotillins for axon regeneration in zebrafish as well as in mammalian cell cultures. Apparently, downregulation of flotillins by flotillin specific morpholinos in the zebrafish resulted in a massive reduction in the number of regenerating axons (60). Since the role of flotillins in neuronal regeneration has recently been directly reviewed, we here omit a long discussion of the topic.…”
Section: In Search Of the Molecular Function Of Flotillinsmentioning
confidence: 99%
“…Their original discovery as "reggies" suggested a function in neuronal regeneration in the goldfish (2,45), which has been later verified by further studies from the same group (57,60,61). However, the regenerative capacity of the optic nerve is poorly conserved in mammals, making a generalization of the regenerative function of flotillins in the nervous system of mammals difficult.…”
Section: In Search Of the Molecular Function Of Flotillinsmentioning
confidence: 99%
“…As an additional control for the specificity of the effect, shR1 cells were transfected with a reggie-1 rescue construct (R1-rescue) which is resistant to the shRNA (Munderloh et al, 2009). The non-rescued cells ( Fig.…”
Section: Reggie-1 Knockdown Affects Fasmentioning
confidence: 99%
“…Reggies were also needed for growth cone formation and elongation (Koch et al, 2013;Munderloh et al, 2009) and the targeted delivery of N-cadherin as one of many growth and guidance receptors (Bodrikov et al, 2011) in elongating neurites. The Rab11/ARF-6 dependent recycling of integrins was demonstrated by Eva and colleagues as an essential molecular mechanism for the regeneration of axons in mammals (Eva et al, 2010(Eva et al, , 2012.…”
Section: Conserved Role Of Reggie In Targeted Delivery Of Cargo?mentioning
confidence: 99%
See 1 more Smart Citation